Influence of platelet activating factor on some physical parameter of frozen Murrah buffalo spermatozoa - KUMAR, SUBODH; SHARMA, ARJAVA (The Indian Journal of Animal Sciences, 2011)
Frozen semen samples of 12 Murrah buffalo bulls with varying conception rates were treated with 200 11M platelet activating factor (PAF) to evaluate its effect on physical parameters of frozen spermatozoa before recommending it as an agent for capacitation. Comparison was made with controls (devoid of Pi) for nlotility., acrosonle reaction, live count and spenn abnornlalities. PAF caused increase in acrOSOlne reaction, head, tail and total abnormalities, decrease in motility and live count while did not affect mid-piece abnormalities. The paired t-test revealed that effect of PAF on all the paranleters except rnid-piece abnonnalities was significant. Â